Maps for the masses? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Now you can make your own monitoring system. Only one hitch: you need a computer. Are you looking for physical details about your area? GIS may have an answer. Geographical Information Systems bring together all sorts of geographic data maps,...